Determinants of a high-quality consultation in medical communications: a systematic review of qualitative and quantitative evidence. Issue 5 (26th August 2019) - Bahadori, Mohammadkarim; Hasanpoor, Edris; Yaghoubi, Maryam; HaghGoshyie, Elaheh
Abstract : Purpose: The medical consultation is one of the requirements in diseases diagnosis and patient treatment. In addition, a high-quality consultation is a fundamental demand of patients, and it is one of the rights of every patient. The purpose of this paper is to identify factors affecting the high-quality consultation in medical communications. Design/methodology/approach: The following electronic databases were searched: MEDLINE (via PubMed), Web of Science, Cochrane, EMBASE, Scopus and ProQuest until December 2018. In addition, the authors searched Google Scholar. Qualitative and quantitative studies were assessed using the Critical Appraisal Skills Programme, Qualitative Checklist and the Center for Evidence-Based Management appraisal checklist, respectively. A stepwise approach was conducted for data synthesis. Findings: Of 3, 826 identified studies, 29 met the full inclusion criteria. Overall, after quality assessment of studies, 25 studies were included. The studies were conducted in the USA ( n =6), the UK ( n =6), the Netherlands ( n =4), Canada ( n =2), Belgium ( n =2), Poland ( n =2), Germany ( n =1), Iran ( n =1), Finland ( n =1), Austria ( n =1), Qatar ( n =1), Denmark ( n =1) and China ( n =1), and five studies were excluded. Data synthesis showed that high-quality consultation consisted of three main categories: structural (4 main themes with 26 sub-themes), process (2 main themes with 33 sub-themes) and outcome (3 main themes with 12 sub-themes) quality. Originality/value: Using the indicators of consultation quality improvement can develop physicians' clinical competence and skills. Decision makers can use them to monitor and evaluate physicians' performance. A high-quality consultation can be useful in social prescribing that helps patients to manage their disease.